INTERACTION OF LASER RADIATION WITH MATTER : Formation of nanoparticles from thin silver films irradiated by laser pulses in air. (26th March 2018) - Nastulyavichus, A A; Smirnov, N A; Kudryashov, S I; Ionin, A A; Saraeva, I N; Busleev, N I; Rudenko, A A; Khmel'nitskii, R A; Zayarnyi, D A
Abstract: Some specific features of the transport of silver nanoparticles onto a SiO2 substrate under focused nanosecond IR laser pulses is experimentally investigated. A possibility of obtaining silver coatings is demonstrated. The formation of silver nanostructures as a result of pulsed laser ablation in air is studied. Nanoparticles are formed by exposing a silver film to radiation of an HTF MARK (Bulat) laser marker (λ = 1064 nm). The thus prepared nanoparticles are analysed using scanning electron microscopy and optical spectroscopy.